Waste pesticide bottles disposal in rural China: Policy constraints and smallholder farmers' behavior. (20th September 2021) - Xu, Xiangbo; Zhang, Zeyang; Kuang, Yujing; Li, Chang; Sun, Mingxing; Zhang, Linxiu; Chang, Dunhu
Abstract: Although Chinese government has made great efforts to control waste pesticide bottles (WPBs) pollution, improper treatment methods adopted by smallholder farmers have caused serious pollution in rural China. Existing studies have shown that institutional design at the government, market and public aspect has a significant impact on farmers' adoption of environmentally friendly treatment methods, while their overall effect and internal relationship remain unexplored hitherto. To address the research gap, 800 households engaged in agricultural production from five representative provinces were used to explore the effect of the current institutional system on impelling farmers to dispose of WPBs ex situ as a whole from three aspects: government environmental regulation, market instrument and personal characteristic, and reveal the relationship between these three aspects of institutional designs, by applying the two-stage Heckman model and moderating effect model. The statistical results showed that among the 670 households using pesticides in agricultural production, 48.80% of households disposed of WPBs in situ, and only 0.30% of households adopted formal treatment method. Other households discarded WPBs with household garbage or sold them to recyclers. The empirical results revealed that regulation stipulations, recycling price, economic compensation and environmental cognition contributed to impel farmers to dispose of WPBs ex situ, among which recycling price had the largest relative effect. However, general village regulations and conventions, specific village regulations on solid waste management, regulation execution and regulation propaganda did not play the role in promoting farmers' adoption of environmentally friendly treatment methods. Besides, only economic compensation exerted synergistic effect on regulation stipulations, and the complementary relationship between economic compensation and environmental cognition was not revealed. Based on the direct and moderating effects of the current institutional system, policy implications were distilled point-to-point to provide reference for policy makers to adjust and optimize the policy formulation and implementation in a timely manner and contribute to the recycling and harmless treatment of WPBs in rural China. Furthermore, the findings also provided first-hand information and new perspective for researchers to understand China's institutional system and internal mechanism. Graphical abstract: Image 1 Highlights: Discarding waste pesticide bottles are causing environmental problems in rural China. 48.80% of households disposed of waste pesticide bottles in situ in rural China. The measures from government and market had positive effect on proper disposal. Soft constraints did not show significant effect. Synergies between the different policies have not yet been achieved.